Psychotherapy with somatosensory stimulation for endometriosis-associated pain: the role of the anterior hippocampus - Beißner, Florian; Popovici, Roxana (Biological psychiatry, 2018)
Background: Endometriosis is a gynecological disorder affecting 6%-10% of all women in their reproductive age. There is an emerging view in the literature that psychological trauma plays a central role in the pathogenesis of pelvic pain, one of the core symptoms of endometriosis. Here we report central nervous system mechanisms of a novel combination of psychotherapy and somatosensory stimulation that has recently shown remarkable effects in reducing pain, anxiety, and depressive symptoms in these patients. Methods: We conducted a randomized controlled trial; 67 patients with severe endometriosis-associated pain (maximum pain: 7.6 ± 2.0, average pain: 4.5 ± 2.0 on a 10-point numeric rating scale) were included in the study and randomly allocated to intervention (35 patients) or waitlist control (32 patients) groups. Resting-state functional magnetic resonance imaging was used to assess brain connectivity of these patients at baseline, after 3 months of therapy, and after 6 months. The analysis focused on the hippocampus. Results: We identified a cortical network comprising the right anterolateral hippocampus—a region modulating the hypothalamic-pituitary-adrenal axis—and somatosensory, viscerosensory, and interoceptive brain regions. Regression analysis showed that reduction in connectivity predicted therapy-induced improvement in patients׳ anxiety. Conclusions: We have identified a putative neurobiological mechanism underlying the potent combination of psychotherapy and somatic stimulation in treating symptoms of endometriosis.
Available online 16 January 2017
Gesehen am 11.03.2020